2017
DOI: 10.1186/s12885-017-3338-x
|View full text |Cite
|
Sign up to set email alerts
|

High lymphatic vessel density and presence of lymphovascular invasion both predict poor prognosis in breast cancer

Abstract: BackgroundLymphatic vessel density and lymphovascular invasion are commonly assessed to identify the clinicopathological outcomes in breast cancer. However, the prognostic values of them on patients’ survival are still uncertain.MethodsDatabases of PubMed, Embase, and Web of Science were searched from inception up to 30 June 2016. The hazard ratio with its 95% confidence interval was used to determine the prognostic effects of lymphatic vessel density and lymphovascular invasion on disease-free survival and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 36 publications
8
26
0
Order By: Relevance
“…We also observed a meaningful correlation with respect to metastatic lymph node involvement between tumour size and lymphovascular invasion. This conclusion was in agreement with the study of Zhang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…We also observed a meaningful correlation with respect to metastatic lymph node involvement between tumour size and lymphovascular invasion. This conclusion was in agreement with the study of Zhang et al [29].…”
Section: Discussionsupporting
confidence: 94%
“…According the current study; significant positive correlation was found between VCAM-1 expression in breast carcinoma and tumor grade and histologic stage. These findings were consistent previous findings that demonstrated that the highest VCAM-1 expression levels were associated with moderately or poorly differentiated tumors and advanced stages of breast carcinoma [2,10]. According to our findings; increased VCAM-1 expression was significantly associated with high incidence of LVI, high rates of LNM suggesting that VCAM-1 is a potential independent prognostic factor for breast carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…When breast cancer cells disseminate through the lymphatic vasculature the first lymph node reached, termed the sentinel, becomes colonised (36). The emerging lymph node metastasis is drained by de novo assembled lymphatic vessels, which perforate the neoplastic tissue (4,37,38). As soon as metastatic cancer cells intravasate these de novo lymphatics they are transported to the efferent lymphatic sinus and colonise downstream lymph nodes until they reach and infest distant organs (4).…”
Section: Discussionmentioning
confidence: 99%